Assessment of local and non–local turbulent flow components on turbulence–flame interaction - Er-Raiy, Aimad; Boukharfane, Radouan; Alzaben, Linda; Parsani, Matteo (Journal of physics. Conference series, 2021)
In the framework of turbulence-flame interaction, the flame is characterized by the gradient of a reactive scalar such as the progress variable, whereas the turbulence is represented by the vorticity and the strain rate. Quantitative assessment of this interaction is performed trough the study of the coupled transport between these quantities that are subject to the effects of heat release and chemical reactions. The present analysis aims at improving the understanding of the small scale turbulence – flame interaction properties, through the introduction of an additive decomposition of the strain rate and vorticity fields into their local and non-local components. The respective role of the local and non-local effects is studied for a broad range of Karlovitz numbers, by virtue of direct numerical simulations (DNS) of turbulent, premixed, lean, and statistically planar flames of methane-air. In the conditions of the present study, the alignment between flame front normals and the strain rate is found to be dominated by the local contribution from the strain rate tensor.